Acetabular cup displacement after polyethylenecement interface failure: A complication of total hip replacement in seven dogs - Hunter, S.; Dyce, J.; Butkus, L.; Olmstead, M. L. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Acetabular cup displacement (ACD) was identified as a complication of cemented modular total hip replacement in seven dogs. ACD is characterized by mechanical failure of the polyethylene-cement interface and subsequent cup migration, and is a clinical entity distinct from classical aseptic loosening. ACD is a sequela of extrusion of the cup and lateralization of the prosthetic load-bearing axis. The acetabular cup displacement ratio (ACDR) has a statistically significant effect on whether ACD develops (P <0.0005). If ACD should occur, acetabular revision arthroplasty generally results in a good clinical outcome, if not complicated by infection.
Keywords: Acetabular cup displacement; total hip replacement